Intelligent Environments Methods, Algorithms and Applications - Monekosso, Dorothy.; Remagnino, Paolo.; Kuno, Yoshinori. (Advanced Information and Knowledge Processing, 2009)
Researchers involved in the Intelligent Environment field are working towards a future where humans live in autonomous and adaptive environments; where public and private spaces are endowed with intelligence that enhances user experience and improves quality of life. Each chapter in the book describes an example of intelligent environment, focussing on the artificial intelligence technique employed to create the environment. The book also introduces engineering solutions to the problem of understanding and modelling complex scenes via multi-modal arrays of sensors. This collection contains contributions from key researchers in the field. Topics covered include: Ontology learning Multi-agent methods Multi-sensor fusion Intelligent human-environment interaction Advanced human-computer interaction Conventional and embedded robotic solutions Ambient representation and innovative sensors This book will be of interest to graduate students and researchers in academia and industry wishing to learn more about ambient intelligence and its potential impact on society.